Cutaneous Adverse Drug Reaction Among HIV-Infected Patients Starting Antituberculosis Treatment - Widhani, Alvina; Karjadi, Teguh Harjono; Yunihastuti, Evy; Salwani, Desi; Pramudita, Angga; Nababan, Saut Horas; Praptini, Mirna Nurasri; Mondrowinduro, Prionggo (UI Scholars Hub, 2022)
Introduction. Treatment of tuberculosis (TB) in HIV patients is complicated due to numerous comorbidities and possible adverse effects. One of which is cutaneous adverse drug reaction (CADR). This adverse event is often difficult to manage because of multiple medications the patients get. The objective of this study was to know the prevalence and risk factors of CADR among HIV-infected patients starting anti-TB treatment. Methods. This retrospective study reviewed data from medical records of new patients at Working Group on AIDS outpatient clinic at Cipto Mangunkusumo Hospital, Indonesia in January 2008-December 2010 that had started anti-TB treatment. Risk factors of CADR among HIV patients treated with antituberculosis drugs evaluated were sex, age, route of HIV transmission, TB manifestation, and baseline CD4+ cell count. Numeric data were analyzed using independent T-test if normally distributed, otherwise Mann Whitney U test were used. Chi-square or Fisher’s exact test were used for categorical data. p-value was considered significant if below 0.05. Results. Of 454 HIV-infected patients that started anti-TB treatment, median age was 30 years. Most patients were male and intravenous drug users/IDU. Median baseline CD4+ cell count was 61 cells/ μL. There were 10.6% subjects that developed CADR. Most common manifestations were maculopapular rashes (66.7%), followed by erythema multiforme (14.6%), and Stevens Johnson Syndrome (8.3%). Anti-TB drugs were stopped and then re-challenge was conducted in 54.2% patients. Anti-TB drugs were continued and only the suspected drug was stopped in 29.2% patients. The offending drugs were cotrimoxazole (41.7%), rifampicine (41.7%), ethambutol (16.7%), pyrazinamide (14.6%), pyrimethamine (12.5%), isoniazide (10.4%), streptomycin (8.3%), efavirenz (8.3%), fixed dose combination of antituberculosis drugs (8.3%), and nevirapine (4.2%). The proportion of CADR was higher in woman than man (12% vs. 10.3%, p=0.66), non-IDU than IDU (13% vs. 9.2%, p=0.20), without extrapulmonary TB than extrapulmonary TB (11.1% vs. 9.4%, p=0.29), but the associations weren’t statistically significant. Median age was higher (31 vs. 30 years, p=0.32) and CD4 cell count (59.5 vs. 62 sel/μL, p=0.96) was lower in CADR group than non CADR group. Conclusion. The prevalence of CADR among HIV-infected patients starting anti-TB treatment was 10.6%. Sex, age, route of HIV transmission, TB manifestation, and baseline CD4+ did not have statistically significant association with CADR.